“FROM INDEPENCE TO WAR”: A CRITICAL ANALYSIS OF FOREIGN HISTORIOGRAPHY ON THE ARMED CONFLICT IN CHECHNYA - Gorusina, Evgenia Mihajlovna; Osmaev, Abbaz Dogievic (History, Archeology and Ethnography of the Caucasus, 2024)
This article analyzes the English-language historiography of the armed conflict in the Chechen Republic. The study employs a periodization approach, which serves as the basis for source analysis and divides the research into two stages: the path towards independence in the wake of the past (1991-1996) and from independence to war (1999-2009). A content analysis of historical works has been conducted. This research aims to elucidate the construction of foreign historiography concerning the most prominent post-Soviet armed conflict, the information about which is often recreated, distorted, and utilized by numerous authors to portray a negative image of the Russian Federation, both past and present. The study reveals that foreign researchers have largely overlooked the relationship between armed violence and collective memory, instead focusing on the dynamics between the republic and the federal center following the collapse of the USSR. The majority of foreign historiography regarding the armed conflict in the region exhibits a negative connotation, is politicized, and contains an assessment of the relationship along the “center-periphery” axis. The study finds that foreign authors describing the period of 1994-1996 shifted their research focus to separatism in Chechnya and its struggle for independence from Russia, taking into account the historical context (beginning with the Caucasian War). It is determined that the mass deportation of 1944 played a decisive role in mobilizing collective memory prior to the outbreak of hostilities in 1994, a topic addressed by virtually all foreign authors. The changed international counter-terrorism agenda following September 11, 2001, resulted in the “Ichkerian” past of Chechnya (1991-1999) being marginalized in public and academic discourse. Foreign works analyzing the armed actions of 1999-2009 began to attract interest for the development of military industry (particularly in the United States). This shift is attributed to terrorism replacing not only traditional warfare but also guerrilla tactics, which were previously widely employed in Chechnya. Foreign authors have observed that since 1999, the image of Chechens has been demonized in public discourse and transformed into that of “mujahideen.”